Prebiotic- and Panthenol-Containing Multipurpose Healing Dermocosmetics Post-Cryotherapy for Actinic Keratoses: Results of a Randomized Controlled Trial - Ariasi, Cesare; Romanò, Carola; Tomasi, Cesare; Soglia, Simone; Licata, Gaetano; Rubelli, Luca; Calzavara Pinton, Piergiacomo; Venturini, Marina; Arisi, Mariachiara (Dermatology Practical & Conceptual, 2025)
Introduction: Actinic keratosis (AK) is a precancerous skin lesion that can progress to keratinocyte carcinoma. Objective: The objective of the study was to evaluate the efficacy of a dermocosmetic (DC) formulation containing prebiotic active ingredients (Aqua Posae Filiformis, a complex made of ferments, sugars, plant extracts, panthenol, madecassoside, and zinc) on healing time and local skin reactions (LSR) following cryotherapy of AKs and to compare the application of DC aand boric acid 3% solution soaks (BA) vs. BA alone. Methods: Seventy-five adult patients presenting with a maximum of 5 isolated AKS on the face and/or scalp and who underwent cryotherapy (T0) were enrolled. Post-treatment, patients initiated the application of BA only or BA followed by DC once daily for 30 days (unblinded 1:1 randomization). The evaluation of efficacy in healing time and cosmetic outcomes was assessed 30 days post-treatment (T2); LSR was evaluated 3 days post-treatment (T1). Results: There was a gain of 4.5 days (40%) in healing time in the BA+DC group compared to the BA group, with a median time of 7 days versus 11.5 days (P<0.0005). Additionally, 50% of lesions in complete response had an excellent cosmetic outcome with BA+DC vs. 20% with BA only. The majority of patients treated with BA+DC had mild LSR vs. moderate LSR with BA, with a median value of 2 vs 3, respectively (P<0.0001). Conclusion: The addition of a prebiotic DC significantly reduced healing time, improved cosmetic outcomes, and minimized LSR post-cryotherapy. No adverse events were reported with this treatment.